2017
DOI: 10.1158/1535-7163.mct-16-0644
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Treatment of Metastatic Breast Cancer by PLK1 siRNA Delivered by an Antioxidant Nanoparticle Platform

Abstract: Metastatic breast cancer is developed in about 20–30% of newly diagnosed early stage breast cancer patients despite treatments. Herein, we report a novel nanoparticle platform with intrinsic anti-metastatic properties for the targeted delivery of Polo-like kinase 1 siRNA (siPLK1). We first evaluated it in a triple negative breast cancer (TNBC) model, which shows high metastatic potential. PLK1 was identified as the top therapeutic target for TNBC cells and tumor initiating cells in a kinome-wide screen. The pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 29 publications
0
38
1
Order By: Relevance
“…In addition, PLK1 inhibition could potentially be a promising strategy to prevent prostate cancer dissemination. Consistent with this notion, a recent study reported that PLK1 depletion, mediated by PLK1 siRNA delivered by an antioxidant nanoparticle platform, inhibits lung metastasis and prolongs overall survival in a mouse model of breast cancer metastasis [ 118 ]. PLK1 inhibition by a small molecule inhibitor hindered brain metastases and prolonged survival in a mouse model of breast cancer brain metastasis [ 119 ].…”
Section: Plk1 As a Key Target For Cancer Therapymentioning
confidence: 76%
“…In addition, PLK1 inhibition could potentially be a promising strategy to prevent prostate cancer dissemination. Consistent with this notion, a recent study reported that PLK1 depletion, mediated by PLK1 siRNA delivered by an antioxidant nanoparticle platform, inhibits lung metastasis and prolongs overall survival in a mouse model of breast cancer metastasis [ 118 ]. PLK1 inhibition by a small molecule inhibitor hindered brain metastases and prolonged survival in a mouse model of breast cancer brain metastasis [ 119 ].…”
Section: Plk1 As a Key Target For Cancer Therapymentioning
confidence: 76%
“…Globally, breast cancer accounted for the highest number of new cancer cases in 2015 (22). Nearly 30% of newly diagnosed patients with early stage breast cancer develop a distant metastasis despite receiving therapy (23). Current therapy options for breast cancer include surgery, hormonal therapy, immunotherapy, chemotherapy, radiation therapy, or a combination of these treatments (24).…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies are those generated from a single cell lineage that bind to a single epitope on their target (as opposed to polyclonal antibodies that are generated by a range of B cells that bind to multiple epitopes on their target). The most commonly used mAb for targeted delivery of siRNA is Trastuzumab, an IgG1 mAb against human epidermal growth factor 2 (HER2) for selective targeting of breast cancer . Another common antibody, useful for targeting the wider epidermal growth factor receptor (EGFR) family is Cetuximab .…”
Section: Selective Tissue Targetingmentioning
confidence: 99%